ANALYSIS OF STUDENTS INTEREST IN CONTINUING THEIR STUDIES: A REVIEW OF PLANNED BEHAVIOR THEORY - Yuliana, Sanita; Bagas Yudhistira Lesmana; Azizah, Nafisa; Shidqi Hizrian, Gesa; Abyan Daffa, Nadhif (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study was conducted to determine the interest of students of SMKN 5 Bandung and SMKN 1 Majalengka to continue their studies at the college level. The method used is descriptive quantitative, by distributing questionnaires to grade XII students at SMKN 5 Bandung and SMKN 1 Majalengka who have majors relevant to the Building Engineering Education Study Program. Data were analyzed based on four aspects, namely attitudes toward behavior, subjective norms, perceived behavioral control, and intentions. The questionnaire was compiled based on these four aspects and distributed to students of SMKN 5 Bandung and SMKN 1 Majalengka. The results of the study showed that most students had a strong intention to continue their studies in college, especially in the Building Engineering Education Study Program. This finding indicates a match between the majors they took at SMK, namely Building Modeling and Information Design (DPIB), with the choice of further study they were interested in. In addition, these results also illustrate that students have a positive view of educational sustainability, supported by the social environment and confidence in their abilities. It is hoped that the results of this study can be used as consideration in the development of career guidance programs in schools and the promotion of relevant study programs in college.